2021
DOI: 10.1088/1742-6596/1833/1/012062
|View full text |Cite
|
Sign up to set email alerts
|

Android application innovation as the indonesian basic spices learning media

Abstract: Education is a significant aspect in the development of a nation. Currently, Indonesia is entering the industrial revolution 4.0 which brings a great impact in various fields, including the field of education as the learning process must continuously evolve by embracing the applications of digital media. However, the learning process in formal education at the moment in Indonesia, especially in vocational high school, tends to use conventional-type media and methods. As a result, students are less enthusiastic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Bollt found that the comprehensive evaluation of tourism resources in most regions still follows the traditional comprehensive evaluation idea, ignoring the characteristic indicators and differences of tourism resource sustainability in different regions [ 7 ]. Through experimental verification, Wulandari and Handayani proposed that the comprehensive evaluation effect of regional tourism resources could not reach the optimal state [ 8 ]. Deb et al put forward an adaptive model for the comprehensive evaluation of regional tourism resources based on multistrategy technology.…”
Section: Related Workmentioning
confidence: 99%
“…Bollt found that the comprehensive evaluation of tourism resources in most regions still follows the traditional comprehensive evaluation idea, ignoring the characteristic indicators and differences of tourism resource sustainability in different regions [ 7 ]. Through experimental verification, Wulandari and Handayani proposed that the comprehensive evaluation effect of regional tourism resources could not reach the optimal state [ 8 ]. Deb et al put forward an adaptive model for the comprehensive evaluation of regional tourism resources based on multistrategy technology.…”
Section: Related Workmentioning
confidence: 99%
“…In the covid-19 pandemic, educators are confused with the learning system that will be used during the study from home (Harnani, 2020). Education is one aspect of the development of a nation (Wulandari, 2021). If the learning system during the study from home is not immediately designed, it can lead to a lost generation (Pantjoro, 2020).…”
Section: Introductionmentioning
confidence: 99%